GA Houses 185. - Futagawa, Yoshio; Saito, Hitomi; Nakamura, Akiyo (Tokyo : A.D.A. EDITA Tokyo Co., Ltd., 2022)
Aires Mateus - House in Barreiro ; Aires Mateus + Miguel Passos de Almeida - House in Campo de Ourique ; Tom Wiscombe - Dark Chalet ; Tomohiro Hata - House in Shinohara ; Wespi de Meuron Romeo Architects - House in San Nazzaro ; Akinori Yoshimura - House in Mihama ; Gregorius Supie Yolodi + Maria Rosantina - Tamarind House ; Gregorius Supie Yolodi + Maria Rosantina / An House ; Antony Liu + Studio Tonton - Y House ; Shigeru Fuse - Ventinove ; Hiroyuki Unemori - Father and Son's House
boek